The oil kings how the U.S., Iran, and Saudi Arabia changed the balance of power in the Middle East - Cooper, Andrew Scott (Simon & Schuster, 2011)
The first expose of the secret U.S.-Saudi plot that broke OPEC and brought down the Shah of Iran